Model Penguatan School Leadership untuk Membangun Budaya Sekolah yang Berkelanjutan - Eka Suhardi; Rina Rosdiana; Rita Istiana; Lufty Hari Susanto; Raihan Naufal Azhar (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
School leadership plays an important role in shaping organizational culture in educational environments. However, in practice, leadership in schools is often understood merely as the activity of giving instructions, so that teacher participation and collaboration have not developed optimally. This community service activity aims to strengthen school leadership by improving participants’ understanding of strategies for influencing organizational members in order to support the formation of a sustainable school culture. The activity was conducted at SMK Negeri 1 Rangkasbitung and involved principals, teachers, and educational staff from several schools in the Rangkasbitung area. The approach used was a participatory approach. The activities were carried out through counseling sessions, interactive discussions, as well as reflection and mentoring related to leadership. The results of the activity show that participants gained a better understanding of influence strategies in leadership and the importance of communication, role modeling, and collaboration in building a sustainable school culture.